2021
DOI: 10.1039/d1an00075f
|View full text |Cite
|
Sign up to set email alerts
|

Feature fusion of Raman chemical imaging and digital histopathology using machine learning for prostate cancer detection

Abstract: The diagnosis of prostate cancer is challenging due to the heterogeneity of its presentations, leading to the over diagnosis and treatment of non-clinically important disease. Accurate diagnosis can directly benefit...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…110 Using a binary classification model, a sensitivity of 73.8% and a specificity of 88.1% were predicted for the G3/G4 classification, while a sensitivity of 54.1% and specificity of 84.7% were obtained using only digital histopathology. 110 Head and Neck Cancer. Zhang et al distinguished between normal (n = 34) and laryngeal squamous cell carcinoma (n = 44) using SRH imaging at only two wavenumbers (2845 and 2930 cm −1 ) in addition to SHG imaging.…”
Section: ■ Raman Spectroscopy For Diagnosticsmentioning
confidence: 95%
See 1 more Smart Citation
“…110 Using a binary classification model, a sensitivity of 73.8% and a specificity of 88.1% were predicted for the G3/G4 classification, while a sensitivity of 54.1% and specificity of 84.7% were obtained using only digital histopathology. 110 Head and Neck Cancer. Zhang et al distinguished between normal (n = 34) and laryngeal squamous cell carcinoma (n = 44) using SRH imaging at only two wavenumbers (2845 and 2930 cm −1 ) in addition to SHG imaging.…”
Section: ■ Raman Spectroscopy For Diagnosticsmentioning
confidence: 95%
“…Doherty et al reported that a combination of digital histopathology and spontaneous Raman imaging may advance the diagnosis of prostate cancer because of incorporating morphological and biochemical information . Using a binary classification model, a sensitivity of 73.8% and a specificity of 88.1% were predicted for the G3/G4 classification, while a sensitivity of 54.1% and specificity of 84.7% were obtained using only digital histopathology …”
Section: Raman Spectroscopy For Diagnosticsmentioning
confidence: 99%
“…Therefore, the instruments need to perform quick data assessments and analysis. Here, first approaches report on the implementation of automated and machine-learning based classification and readout options [ 273 , 274 , 275 ], which will be an inevitable task in the future, especially when multimodal imaging approaches and conventional imaging tools will be combined in the surgery room.…”
Section: Challenges and Limitationsmentioning
confidence: 99%
“…The core of this algorithm is a feature fusion algorithm that can automatically adjust the proportion of high-level DL features and traditional features ( 20 ). Similarly, the fusion of digital histopathology and Raman chemical imaging modalities has the potential to improve the binary classification of prostate cancer pathology images by integrating both morphological and biochemical information across data sources ( 21 ). Most recently, to mine more information from different radiomics data in multicenter studies and identify personalized predictive and/or prognostic models to improve the reproducibility, an image biomarker standardization initiative (IBSI) was introduced for the standardization of radiomic features ( 22 ), and some radiomics computational frameworks were developed to comply IBSI and allow users to complete the whole radiomics workflow within the same software, simplifying the radiomics process, such as the matRadiomics software ( 23 ).…”
Section: Introductionmentioning
confidence: 99%